Positive end expiratory pressure in acute hypoxemic respiratory failure due to community acquired pneumonia: do we need a personalized approach? - Valentina Paolini; Paola Faverio; Stefano Aliberti; Grazia Messinesi; Giuseppe Foti; Oriol Sibila; Anna Monzani; Federica De Giacomi; Anna Stainer; Alberto Pesci (PeerJ, 2018)
Background Acute respiratory failure (ARF) is a life-threatening complication in patients with community acquired pneumonia (CAP). The use of non-invasive ventilation is controversial. With this prospective, observational study we aimed to describe a protocol to assess whether a patient with moderate-to-severe hypoxemic ARF secondary to CAP benefits, in clinical and laboratoristic terms, from the application of a positive end expiratory pressure (PEEP) + oxygen vs oxygen alone. Methods Patients who benefit from PEEP application (PEEP-responders) were defined as those with partial pressure of arterial oxygen to the fraction of inspired oxygen (PaO2/FiO2) increase >20% and/or reduction of respiratory distress during PEEP + oxygen therapy compared to oxygen therapy alone. Clinical characteristics and outcomes were compared between PEEP-responders and PEEP-non responders. Results Out of 41 patients, 27 (66%) benefit from PEEP application (PEEP-responders), the best response was obtained with a PEEP of 10 cmH2O in 13 patients, 7.5 cmH2O in eight and 5 cmH2O in six. PEEP-responders were less likely to present comorbidities compared to PEEP-non responders. No differences between groups were found in regards to endotracheal intubation criteria fullfillment, intensive care unit admission and in-hospital mortality, while PEEP-responders had a shorter length of hospital stay. Discussion The application of a protocol to evaluate PEEP responsiveness might be useful in patients with moderate-to-severe hypoxemic ARF due to CAP in order to personalize and maximize the effectiveness of therapy, and prevent the inappropriate PEEP use. PEEP responsiveness does not seem to be associated with better outcomes, with the exception of a shorter length of hospital stay.